Factors affecting utilization of health facilities for labour and childbirth: a case study from rural Uganda - Dantas, Jaya A R; Singh, D.; Lample, M. (BMC, 2020)
BACKGROUND: Since 2000 considerable attention has been placed on maternal health outcomes as the 5th Millennium Goal. In Uganda, only 65% of births are delivered by a skilled birth attendant, contributing to the 435 women that die in every 100,000 births from unattended complications. Factors that impact a women's decision on where to deliver include cost and household barriers, poor health services and lack of education.